2015
DOI: 10.1590/abd1806-4841.20153385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the social, clinical and laboratorial profile of patients diagnosed with leprosy in a reference center in São Paulo

Abstract: BACKGROUNDLeprosy is the main infectious cause of disability. It is said to be eradicated in São Paulo since 2005, but diagnosis is still late.OBJECTIVESTo investigate the social, clinical and laboratorial profile of leprosy patients diagnosed between 01/2007 and 12/2011, in a reference center in São Paulo.METHODSRetrospective descriptive study. Data of all new leprosy cases diagnosed between 01/2007 and 12/2011 were raised in São Paulo.RESULTS103 men and 71 women were diagnosed, most of them were multibacilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 21 publications
3
11
0
7
Order By: Relevance
“…The later the diagnosis is performed, higher the risk of presenting deformities. An early diagnosis is the most effective way to avoid permanent damage, and the onset of deformity is more time-bound than the control actions of the disease (Porto et al, 2015;Monteiro et al, 2017b;Costa et al, 2019). Our results show that the leprosy diagnosis has been set earlier and the strategies of prevention and control of the disease are more effective than the past.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The later the diagnosis is performed, higher the risk of presenting deformities. An early diagnosis is the most effective way to avoid permanent damage, and the onset of deformity is more time-bound than the control actions of the disease (Porto et al, 2015;Monteiro et al, 2017b;Costa et al, 2019). Our results show that the leprosy diagnosis has been set earlier and the strategies of prevention and control of the disease are more effective than the past.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of leprosy occurs from intimate and prolonged contact of a susceptible individual with a bacilliferous patient through bacilli inhalation. The best way to stop transmission is early diagnosis and treatment (Porto et al, 2015;Anchieta et al, 2019). Leprosy manifests mainly through dermato-neurological signs and symptoms such as skin and peripheral nerves lesions, especially the medial, radial, ulnar, tibial, fibular and facial nerves (Duarte-Cunha et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 17 Regarding leprosy, a descriptive study conducted in the state of São Paulo revealed that this disease predominates in men. 18 Lastly, considering the main differential diagnosis of neoplastic etiology, a case-control study performed in the South region of Brazil showed that BCC diagnosis prevails among women (n = 74, 58.2%). 19 However, other studies involving larger series around the world revealed higher prevalence of BCC in men.…”
Section: Discussionmentioning
confidence: 99%
“…Disabilities can affect children occupationally which can affect them economically in their future. 6 Moreover the various risk factors associated with leprosy patients and their contacts are still not clearly known. Only through intensive research helps in examination of group-level and individual level factors.…”
mentioning
confidence: 99%